2005
DOI: 10.1007/s11136-004-3919-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors and Health-Related Quality of Life in Hemodialysis Patients

Abstract: Several sociodemographic and clinical variables are known to influence the health-related quality of life (HRQOL) of patients with kidney disease, yet the relationship between psychological factors and the HRQOL measured by the Kidney Disease Quality of Life Short-Form (KDQOL-SF) is incompletely understood. The objective of this study was to examine the relationship between psychosocial status (depressive symptoms, trait anxiety, and social support) and KDQOL-SF scales in hemodialysis (HD) patients by controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
3
25

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 24 publications
10
87
3
25
Order By: Relevance
“…The largest weighted mean correlations were recorded in the physical function, vitality, and physical component scores. We identified two studies that measured the correlations between Hct and KDQOL scores (9,29). Vazquez et al (9) found that Hct correlated significantly with patient satisfaction, effects of kidney disease, and quality of social interaction scales of the KDQOL; however, Hct did not significantly correlate with the cognitive function, sexual function, sleep, social support, symptom, or burden of kidney disease scales (9).…”
Section: Results Stratified By Traditional Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest weighted mean correlations were recorded in the physical function, vitality, and physical component scores. We identified two studies that measured the correlations between Hct and KDQOL scores (9,29). Vazquez et al (9) found that Hct correlated significantly with patient satisfaction, effects of kidney disease, and quality of social interaction scales of the KDQOL; however, Hct did not significantly correlate with the cognitive function, sexual function, sleep, social support, symptom, or burden of kidney disease scales (9).…”
Section: Results Stratified By Traditional Biomarkersmentioning
confidence: 99%
“…We identified two studies that measured the correlations between Hct and KDQOL scores (9,29). Vazquez et al (9) found that Hct correlated significantly with patient satisfaction, effects of kidney disease, and quality of social interaction scales of the KDQOL; however, Hct did not significantly correlate with the cognitive function, sexual function, sleep, social support, symptom, or burden of kidney disease scales (9). In contrast, Carmichael et al (29) found a statistically significant adjusted correlation between Hct and the quality of social interaction scale of the KDQOL (r ϭ 0.21) but no significant correlations with any other diseasetargeted scales.…”
Section: Results Stratified By Traditional Biomarkersmentioning
confidence: 99%
“…The support can be provided in the form of psychological, emotional, informational, tangible and sociable support (17). In fact, reducing their tension in patients requires identification of the sources of social support in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vázquez ve ark. [18] yaptıkları çalımada böbrek hastalı¤ı ve HD'nin hastaların yaam kalitesine etkisine baktıklarında en çok genel sa¤lık algısı, fiziksel-rol alanı ve enerji alanında etkilendiklerini saptamılardır.…”
Section: Tartimaunclassified